(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Anaemia is a serious health concern across the globe. India, especially Assam is not exception to it. Anaemia may cause maternal mortality and prenatal mortality. In addition it also increases risk of premature delivery and low birth weights. Anaemia among children may lead to other health problems in future to make life redundant, it reduces human productivity and causes poor level of concentration. The present study will try to analyse the incidence of anaemia among women in Assam, India. For that matter the study is based on secondary data which are collected from different reports published by government and non-government agencies. We find that anaemia has remained a chronic problem in the state. However, it is more prominent among women and girls are also prone to become more anaemic